2009
DOI: 10.1007/s00134-009-1658-2
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ characterization, hospital course and clinical outcomes in five Italian respiratory intensive care units

Abstract: The clinical outcomes of our units worsened over 15 years, likely as consequence of admitting more severely ill patients. The potential further negative influence of reduced medical staff availability on weaning success, home discharge and LOS warrants future prospective investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
1
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 22 publications
6
43
1
13
Order By: Relevance
“…15 The clinical outcome of patients requiring ICU admission (the stepdown pattern) has been described in the recent literature, especially for the subset of patients requiring prolonged mechanical ventilation and transferred to a RICU located inside a rehabilitation center or long-term acute care hospital, which is increasingly utilized after a critical illness, especially in North America. 16,17 Data collected on more than 3,000 patients admitted to 5 Italian RICUs, mainly dedicated to weaning from mechanical ventilation, showed a mortality rate of about 15%, 18 which is in line with our results. Concerning a RICU located inside an acute care hospital, Bigatello et al 19 suggested that a considerable number of patients were ready to come off mechanical ventilation at the time of RICU admission, implying that in the preceding ICU stay, discontinuing mechanical ventilation had not always been a priority, and explaining the quite low mortality rate even 1 year after hospital admission.…”
Section: Discussionsupporting
confidence: 89%
“…15 The clinical outcome of patients requiring ICU admission (the stepdown pattern) has been described in the recent literature, especially for the subset of patients requiring prolonged mechanical ventilation and transferred to a RICU located inside a rehabilitation center or long-term acute care hospital, which is increasingly utilized after a critical illness, especially in North America. 16,17 Data collected on more than 3,000 patients admitted to 5 Italian RICUs, mainly dedicated to weaning from mechanical ventilation, showed a mortality rate of about 15%, 18 which is in line with our results. Concerning a RICU located inside an acute care hospital, Bigatello et al 19 suggested that a considerable number of patients were ready to come off mechanical ventilation at the time of RICU admission, implying that in the preceding ICU stay, discontinuing mechanical ventilation had not always been a priority, and explaining the quite low mortality rate even 1 year after hospital admission.…”
Section: Discussionsupporting
confidence: 89%
“…6 Moreover, a relevant-even if minor-number of RHDCUs were located in a rehabilitation centers, which, differently from those belonging to the hospitals, work as step-down units for ICUs, as they are mostly dedicated to the care of difficult to wean and tracheostomized patients. 23 For more than one fifth of the surveyed RHDCUs, there was not an ICU located within the same institution; this is a critical point about RMUs, which are not able to manage severely ill patients needing invasive monitoring and/or ventilation.…”
Section: Number Geographic Distribution Institutionmentioning
confidence: 99%
“…3,11,12 In particular, patients may receive a prompt and dedicated physiotherapy rehabilitation program in chronic ventilator facilities, 1,3,13 and transfer from an ICU to a chronic ventilator facility substantially improved patients' ambulation and activities of daily life irrespective of the underlying pathophysiology, avoiding unnecessary immobilization 14 . To date, the role of comprehensive rehabilitation in critically ill adults still remains controversial 13 or not fully established 15 : patients who have survived a recent acute respiratory failure (ARF) event can benefit from an individually tailored physiotherapy rehabilitation program that improves clinical indices, respiratory and peripheral muscle strength, activities of daily life, exercise tolerance, and disability scores. 14,[16][17][18][19][20][21][22][23][24] Once the precipitating cause of the ARF episode has been solved, these chronically ill patients still require care due to their huge motor disabilities, clinical dependence (oxygen, mechanical ventilation, nutritional, and communication device needs), and nursing necessities, 3 which the care team (physiotherapist, doctor, and nurse) must measure to better guide the daily care of the patient. No study has been performed with a large patient sample to investigate patient needs with these 3 different perspectives combined.…”
Section: Introductionmentioning
confidence: 99%